Evaluation of UroVysion for Urachal Carcinoma Detection - Hu, Zhiquan; Ke, Chunjin; Liu, Zheng; Zeng, Xing; Li, Song; Xu, Hua; Yang, Chunguang (Frontiers in Medicine, 2020)
Background: Patients with haematuria who are positive for urine fluorescence in situ hybridization (FISH) are generally considered to have urothelial carcinoma. We determined whether UroVysion FISH could be used for the diagnosis of urachal carcinoma. Methods: Seven cases of urachal carcinoma with haematuria subjected to FISH analysis were retrospectively analysed in our hospital from May 2012 to November 2019. Paraffin-embedded tissue sections from 1 FISH-positive and 1 FISH-negative urachal carcinoma were processed in strict accordance with the instructions of the UroVysion kit. Meanwhile, FISH data from the other 414 haematuria patients were collected as controls. Results: All 7 patients with urachal carcinoma were diagnosed with adenocarcinoma. According to the Sheldon stage, 6 patients had stage IIIa and 1 patient had stage IVb. The sensitivity and specificity of urinary FISH for the diagnosis of urachal carcinoma were 71.43% (5/7) and 94.61% (281/297), respectively. The rates of polysomy for chromosomes 3 and 7 in positive patients were both 100% (5/5), while the rate of polysomy for chromosome 17 was 40% (2/5), and the GLPp16 gene deletion rate was 20% (1/5). Histological assessment and cytological FISH were consistent for urachal carcinoma. No significant difference was observed in the diagnostic efficacy between urachal carcinoma and urothelial carcinoma (71.43% VS 87.18%, P=0.245). Conclusions: Taken together, UroVysion FISH is a sensitive and specific method to diagnose urachal carcinoma of late stage with haematuria. Its chromosomal aberrations are different from those of urothelial carcinoma, which may aid in their differential diagnosis.